The Representation of Amy Tan's Background in Her Novel The Joy Luck Club - Mardliya Pratiwi Zamruddin (ELS Journal on Interdisciplinary Studies in Humanities, 2019)
Discourse stylistics focuses upon the largely implicit and highly ideological ‘background’ of the text. Mind style that is one of the traits of stylistics is going to be taken into account of doing the analysis since this research aims to find out about how the mind style of Amy Tan is shaped by her background in her way of writing and producing the novel The Joy Luck Club. The term ‘mind style’ (Leech and Short, 2007) is particularly appropriate where the choices made are consistent through a text or part of a text.  This research is questioned whether or not Amy Tan’s Chinese background have influenced the novelist’s style as represented in her novel, The Joy Luck Club. This research describes the novel with a focus on the characters’ mind style in a stylistic and narrative approach. This research aims to attain the influence from the backgrounds of the novelist and the way the background affect the novelist’s style in producing literary work. The descriptions and explanations of scrutinizing the novel are hoped to provide examples of doing discourse stylistics to literary works. The specific use of Chinese words, the repetition use of pronouns, the presentation of Chinese superstitions have put so much contributions in shaping Amy Tan’s style in her works. Through her literary works, the novelist is able to show her readers linguistic journey through her wordplay style.